2017
DOI: 10.3892/ijo.2017.3842
|View full text |Cite
|
Sign up to set email alerts
|

A 22q11.2 amplification in the region encoding microRNA-650 correlates with the epithelial to mesenchymal transition in breast cancer primary cultures of Mexican patients

Abstract: Breast cancer ranks first in incidence and mortality in working age women. Cancer initiation and progression relies on accumulation of genetic and epigenetic aberrations that alter cellular processes, among them, epithelial to mesenchymal transition (EMT) denotes particularly aggressive neoplasias given its capacity to invade and metastasize. Several microRNAs (miRNA) have been found able to regulate gene expression at the core of EMT. In this study, the Affymetrix CytoScan HD array was used to analyze three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Based on our previous findings on Mexican BRCA samples with a common Amp-650 [ 12 ], we considered that this alteration may be enriched in Hispanic population, however, there was no statistical difference in Amp-650 frequencies between Hispanic (10.26%) and non-Hispanic populations (12.7%) ( Figure 1 a). Additionally, since we had observed a correlation between Amp-650 and EMT features, we thought that Amp-650 should be enriched in BRCA subtypes with known poor clinical outcomes and increased mesenchymal markers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previous findings on Mexican BRCA samples with a common Amp-650 [ 12 ], we considered that this alteration may be enriched in Hispanic population, however, there was no statistical difference in Amp-650 frequencies between Hispanic (10.26%) and non-Hispanic populations (12.7%) ( Figure 1 a). Additionally, since we had observed a correlation between Amp-650 and EMT features, we thought that Amp-650 should be enriched in BRCA subtypes with known poor clinical outcomes and increased mesenchymal markers.…”
Section: Resultsmentioning
confidence: 99%
“…We previously observed Amp-650 in BRCA samples derived from Mexican patients with mesenchymal/invasive tumors [ 12 ]. Here, we explored public databases to assess whether Amp-650 was a recurrent event in BRCA, and whether we could support an important role specific for aggressive subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies described the involvement of miR-650 expression in the poor prognosis of various cancers [ 21 , 22 ]. In BC, the miR-650 amplification has been recently suggested to be involved in triggering EMT [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the latter case, it has been demonstrated that miR-650 confers chemoresistance to docetaxel, an anti-cancerous drug (127). miR-650 can also trigger epithelial to mesenchymal transition in breast cancer by targeting ING4 and NDRG2 (128). Furthermore, several other miRNAs are able to inhibit ING4 expression in cancers.…”
Section: Several Mirnas Have Been Found To Decrease the Expression Ofmentioning
confidence: 99%